INTERPRETATION ON THE TEXT OF APOSTOLIC TRADITION ARTICLE 41 AND THE IMPLICATION FOR TOGETHERNESS - Ricky Pramono Hasibuan; Tony Wiyaret Fangidae; Ricky Pramono Hasibuan (Jurnal Lektur Keagamaan, 2022)
ABSTRACT   This article interprets a text of The Apostolic Tradition, a 3rd century Church Order containing rules for ordination, communion, catechism and baptism, as well as daily prayers. Studies of this ancient text were still very few in Indonesia, and mostly concerned with the part of the communion. In this article, the author will examine daily prayer, specifically the text of Apostolic Tradition 41:1-4 on the dawn prayer. The passage instructed that the congregation must gather every morning to listen to the teachings and perform communal prayer. This research started from fact that there were few daily prayer celebrations in Indonesian churches, especially communal morning prayer. This study employed qualitative study design through literature studies and hermeneutics. The author argues that the communal dawn prayer in the Apostolic Tradition is relevant to be developed in Indonesian context. Keywords: dawn prayer, congregation, Apostolic Tradition   ABSTRAK Artikel ini akan mengulas tentang The Apostolic Tradition atau Tradisi Apostolik, sebuah Tata Gereja Kuno abad ketiga yang berisi aturan tentang penahbisan, perjamuan, katekisasi dan baptisan, serta ibadah harian. Studi tentang teks kuno ini masih sangat minim di Indonesia, dan kajian-kajian seputar Tradisi Apostolik lebih banyak membahas tentang perjamuan. Dalam artikel ini, penulis akan membahas tentang ibadah harian, secara khusus teks Tradisi Apostolik 41:1-4 tentang doa fajar. Di dalam teks tersebut diinstruksikan agar umat setiap subuh bersekutu untuk mendengarkan pengajaran dan melaksanakan doa berjemaah. Studi ini berangkat dari fenomena minimnya ibadah harian di Indonesia, apalagi doa pagi berjamaah. Metode penulisan artikel ini menggunakan kaidah kualitataif, melalui studi literatur dan hermeneutika. Penulis berargumen bahwa keberjamaahan doa fajar dalam Tradisi Apostolik relevan untuk dikembangkan dalam ibadah harian di Indonesia.  Kata kunci: Doa Fajar, Keberjemaahan, Tradisi Apostolik